Fungal and bacterial oxylipins are signals for intra- and inter-cellular communication within plant disease - Beccaccioli, Marzia; Pucci, Nicoletta; Salustri, Manuel; Scortichini, Marco; Zaccaria, Marco; Momeni, Babak; Loreti, Stefania; Reverberi, Massimo; Scala, Valeria (Frontiers in Plant Science, 2022)
Lipids are central at various stages of host–pathogen interactions in determining virulence and modulating plant defense. Free fatty acids may act as substrates for oxidizing enzymes [e.g., lipoxygenases (LOXs) and dioxygenases (DOXs)] that synthesize oxylipins. Fatty acids and oxylipins function as modulators of several pathways in cell-to-cell communication; their structural similarity among plant, fungal, and bacterial taxa suggests potential in cross-kingdom communication. We provide a prospect of the known role of fatty acids and oxylipins in fungi and bacteria during plant–pathogen interactions. In the pathogens, oxylipin-mediated signaling pathways are crucial both in development and host infection. Here, we report on case studies suggesting that oxylipins derived from oleic, linoleic, and linolenic acids are crucial in modulating the pathogenic lifestyle in the host plant. Intriguingly, overlapping (fungi-plant/bacteria-plant) results suggest that different inter-kingdom pathosystems use similar lipid signals to reshape the lifestyle of the contenders and occasionally determine the outcome of the challenge.